Thin-Section CT Characteristics and Longitudinal CT Follow-up of Chemotherapy Induced Interstitial Pneumonitis: A Retrospective Cohort Study. Issue 2 (January 2016) - Lee, Han Na; Kim, Mi Young; Koo, Hyun Jung; Kim, Sung-Soo; Yoon, Dok Hyun; Lee, Jae Cheol; Song, Jin Woo
Abstract : Abstract: To describe the computed tomography (CT) features of chemotherapy-induced interstitial pneumonitis (CIIP) with longitudinal follow-up. The study was approved by the local ethics committee. One hundred consecutive patients with CIIP between May 2005 and March 2015 were retrospectively enrolled. The initial CT was reviewed by 2 independent chest radiologists and categorized into 1 of 4 CT patterns in accordance with the 2013 guidelines for idiopathic interstitial pneumonia: nonspecific interstitial pneumonia (NSIP), organizing pneumonia (OP), hypersensitivity pneumonitis (HP) mimicking desquamative interstitial pneumonitis, and diffuse alveolar damage (DAD). We assessed semiquantitative analysis on a 5% scale to assess the extent of parenchymal abnormalities (emphysema, reticulation, ground-glass opacity, consolidation, honeycombing cyst) and their distribution on initial (n = 100), subsequent (n = 87), and second follow-up CT (n = 48). Interval changes in extent on follow-up CT were compared using paired t test. The clinic-radiologic factors were compared between Group 1 (NSIP and OP patterns) and Group 2 (HP and DAD patterns) using χ 2 and independent t tests. The most common pattern of CIIP on the initial CT was HP (51%), followed by NSIP (23%), OP (20%), and DAD (6%). Diffuse ground-glass opacity was the most common pulmonary abnormality. The predominant distribution was bilateral (99%) and symmetric (82%), with no craniocaudal (60%) or axial (79%) dominance. Subsequent and second follow-up CTs showed decreased extent of total pulmonary abnormalities ( P  < 0.001, respectively). In comparison with Group 1 CIIP, Group 2 CIIP was more likely to be caused by molecularly targeted drugs ( P  = 0.030), appeared earlier ( P  = 0.034), and underwent more complete resolution ( P  < 0.001). Use of a CT pattern–recognition approach to CIIP is appropriate and practical in interpreting radiological findings. Abstract : Supplemental Digital Content is available in the text